Mathematical Modeling of Liquid Slag Layer Fluctuation and Slag Droplets Entrainment in a Continuous Casting Mold Based on VOF-LES Method - Zhao Peng; Li Qiang; Kuang Shi Bo; Zou Zongshu (High Temperature Materials and Processes, 2017)
The slag behaviors, directly relating with the qualities of the final cast products, are influenced by the transient surface flow of liquid steel in a continuous casting mold. A one-half scale model is used to investigate the slag behaviors and their droplets entrainment. The model based on Volume of Fluid (VOF) multiphase coupled with Large Eddy Simulation (LES) is established to further illuminate the phenomena of the liquid oil layer fluctuation, the slag “eye” regions, and the slag entrainment observed in water experiment. The effects of casting speeds on the slag behaviors and their entrained droplets are investigated. The results show that the fluctuation of the oil layer is influenced by the transient flow. The calculations for the oil layer profile, the accumulation, and protrusions of oil layer are consistent with the water experiment. The asymmetry of the slag “eye” regions is also influenced by the asymmetry of free surface and transient turbulent flow. The “eye” regions near the narrow wall show distinct asymmetric change at different casting speeds. At a lower casting speed, the slag “eye” regions change irregularly and display the alternate process of open and collapse at the two sides of the narrow walls of the model. While at a relative higher casting speed, the slag layer gathers toward the nozzle, and the slag “eye” regions gradually grow and always open. The simulation model can reveal that the mechanism of the slag entrainment includes two main modes: the cutting or dragging mode and shear layer instability. The average diameter and amount of the entrained droplets are calculated through the UDF codes of ANSYS FLUENT software, and the size distribution of the entrained droplets is also counted. When the casting speed is lower, the dominant diameters of the entrained droplets range between 2 and 3 mm. With casting speed increase, the distribution of the droplets becomes wider, and there is a gradually increase in the percentage of larger droplets with a size of 4–6 mm.